FRI0052 Serum level of total adiponectin independently predicts rapid radiographic disease progression in early rheumatoid arthritis: a cohort study. (23rd January 2014) - Sellam, J.; Kotti, S.; Meyer, M.; Fellahi, S.; Bastard, J.-P.; Meyer, O.; Lioté, F.; Simon, T.; Capeau, J.; Berenbaum, F.
Abstract : Background: Adipokines have recently emerged as pro-inflammatory mediators involved in the pathophysiology of rheumatoid arthritis (RA). Objectives: To determine whether serum adipokine levels independently predicted early rapid radiographic disease progression (RRP) in early RA. Methods: ELISA was used to assess baseline serum levels of total adiponectin, leptin and visfatin/NAMPT in the 632 patients from the French ESPOIR cohort who met the American College of Rheumatology-European League Against Rheumatism criteria for RA. We tested the association of serum adipokine levels and RRP defined as a change ≥ 5 in total Sharp-van der Heijde Score between inclusion and 1 year (ΔSHS≥5) corresponding to the destruction of one small joint (1 ) in univariate analysis and also after adjusting for all pertinent confounders (age, sex, body-mass-index, insulin resistance log(HOMA-IR), C-reactive protein level (logCRP), DAS28, log(HAQ score), rheumatoid factor and anti-CCP antibodies status, steroid use and radiographic evidence of RA damage at inclusion. Sensitivity versus the false positive frequency (1-specificity) for predicting radiographic disease progression with adiponectin levels was analysed by a receiver-operated characteristic (ROC) curve. The optimal cut-off point of adipokines level to identify patients with RRP was calculated using Youden index. Results: In univariate analyse, there was a trend for association between serum level of adiponectin and RRP (odds ratio OR [95%confidence interval]=1.47 [0.98-2.20]; p=0.06). In multivariate model, serum adiponectin level was independently associated with ΔSHS≥5 (adjusted OR=2.0 [1.14-3.52], p=0.0165) (Table ). Conversely, leptin level was associated with RRP only in univariate analyse (OR=0.73 [0.54-0.97]; p=0.03) and visfatin/NAMPT level displayed no association. Considering the ROC curve, the best serum adiponectin cut-off value level to predict ΔSHS ≥ 5 was 1.60 μg/mL (sensitivity=0.74 and specificity=0.73 and area under the ROC curve=0.76). Conclusions: Serum adiponectin level is a simple and useful biomarker predicting early RRP in early RA independently of RA-confounding factors and metabolic status. Using the threshold of 1.6 μg/mL, patients with early RA at increased risk of early RRP can be identified. References: Vastesaeger N et al. Rheumatology(Oxford) 2009, 48:1114-21 Disclosure of Interest: None Declared